Resonating Culture: Ethnomusicological Theories Unveiling Zhuhu Music in Yangxin Tea-picking Opera of China - Chengyao, Duan; Abdullah, Mohd Hassan (Grenek: Jurnal Seni Musik, 2024)
More than a century ago, the enchanting tea-picking songs enjoyed widespread popularity among the residents of Yangxin in China. These songs served as a source of entertainment within the tea plantation quarters. Folk music artists subsequently reworked these melodies, transforming them into short tunes for collective singing and dancing during the Lantern Festival. The integration of Huangmei tea-picking opera with the "lantern opera" further shaped the musical identity of Yangxin tea-picking opera. This research aims to analyze the features of zhuhu music and its contribution to the musical culture of the Yangxin community, with a particular emphasis on analyzing the music's characteristics and its cultural significance. The study will also delve into the evolving status of zhuhu music within contemporary Yangxin society. Employing an ethnographic research design, I combines participant observation and interviews with her own field experiences to provide a comprehensive account of traditional zhuhu performance practices in Yangxin tea-picking opera. Through a musicological analysis of zhuhu's repertoire, the paper uncovers the uniqueness of zhuhu music and traces changes in its traditional form, style, and function, linking these shifts to broader socio-cultural transformations. In approaching the study of this musical performance, I draw upon theories from the field of ethnomusicology. Building on my preliminary investigation of zhuhu music, I shaped the study by considering theoretical insights from various scholars and incorporating my perspectives. The paper will discuss pertinent theories applied to analyze the music of zhuhu as it accompanies Yangxin tea-picking opera. This research not only contributes to ethnomusicological theory and methodology but also deepens our understanding of the musical culture surrounding Yangxin tea-picking opera in China.